2019
DOI: 10.1038/s41398-019-0395-8
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal networks dynamically related to recovery from major depressive disorder: a longitudinal pharmacological fMRI study

Abstract: Due to lacking predictors of depression recovery, successful treatment of major depressive disorder (MDD) is frequently only achieved after therapeutic optimization leading to a prolonged suffering of patients. This study aimed to determine neural prognostic predictors identifying non-remitters prior or early after treatment initiation. Moreover, it intended to detect time-sensitive neural mediators indicating depression recovery. This longitudinal, interventional, single-arm, open-label, phase IV, pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 89 publications
3
29
1
Order By: Relevance
“…fMRI, including resting-state and task-based fMRI, can divide the brain into self-related regions, such as the anterior cingulate cortex, posterior cingulate cortex, medial prefrontal cortex, precuneus, and dorsomedial thalamus. Many previous studies have shown the disturbance of several brain areas and intrinsic neural networks in patients with depression which could be rescued by antidepressants [113][114][115][116]. Further, some evidence also showed an association between brain network dysfunction and the clinical correlates of patients with depression, including clinical symptoms [117] and the response to antidepressants [118,119], ECT [120,121], and repetitive transcranial magnetic stimulation [122].…”
Section: Brain Imaging and Neuroimaging Studiesmentioning
confidence: 96%
“…fMRI, including resting-state and task-based fMRI, can divide the brain into self-related regions, such as the anterior cingulate cortex, posterior cingulate cortex, medial prefrontal cortex, precuneus, and dorsomedial thalamus. Many previous studies have shown the disturbance of several brain areas and intrinsic neural networks in patients with depression which could be rescued by antidepressants [113][114][115][116]. Further, some evidence also showed an association between brain network dysfunction and the clinical correlates of patients with depression, including clinical symptoms [117] and the response to antidepressants [118,119], ECT [120,121], and repetitive transcranial magnetic stimulation [122].…”
Section: Brain Imaging and Neuroimaging Studiesmentioning
confidence: 96%
“…In addition to the reward circuitry (Cho et al, 2013), we also decided to test the central‐executive network (CEN; Seeley et al, 2007) due to its importance in emotion regulation (Etkin et al, 2015). Hence, ROIs selected from the CONN toolbox's atlas (Cho et al, 2013; Supporting Information, Section 5, Table S2) covered key regions consistently related to a suboptimal course in previous prediction studies (Meyer et al, 2019; Phillips et al, 2015). ROI‐to‐ROI group analysis was based on correlation matrices between the averaged BOLD time courses of ROI pairs (Nieto‐Castanon, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The rate of MDD patients who achieve full remission but continue to have residual symptoms is up to 80% (Nierenberg et al, 1999) often requiring long‐term maintenance treatment to forestall recurrent episodes (National Collaborating Centre for Mental Health (UK), 2010). While the majority of predictive imaging studies have explored determinants of remission from MDEs (Meyer et al, 2019; Phillips et al, 2015), stratification informed by the neurobiology of chronicity, specifically in terms of recurrent MDE and impairing residual symptoms, remains elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14 In human, neuroimaging evidence supports a normalization of the prefrontal cortex dysfunction in those MDD/TRD subject that responds to any antidepressant treatment. 15,16 Renormalization of hippocampal structural deficit was observed in TRD patients following augmentation therapies such as vagus nerve stimulation 17 or ECT. 18 Reduced DA neurotransmission in ventral striatum, amygdala, and hippocampus associated to anhedonia was observed in MDD/TRD patients and rodents exposed to chronic stress.…”
Section: Reversibility Of Neural Plasticity By Treatment In Specific mentioning
confidence: 99%